2018
DOI: 10.1590/s1806-37562017000000379
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhidrosis: prevalence and impact on quality of life

Abstract: Although the prevalence of self-reported excessive sweating was greater than 2%, the actual prevalence of primary hyperhidrosis in our sample was 0.93% and nearly 50% of the respondents with primary hyperhidrosis reported impaired quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 25 publications
5
31
0
3
Order By: Relevance
“…We found axillary site participation to be the most frequent, in accordance to the German and Swedish studies [7, 12] and in contrary to three Brazilian studies [8, 13, 19]. We found palmar PH to be slightly more prevalent than plantar PH, in accordance to studies in Brazil [13, 19], whereas the studies in Germany and Sweden found plantar hyperhidrosis to be slightly more prevalent than palmar hyperhidrosis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We found axillary site participation to be the most frequent, in accordance to the German and Swedish studies [7, 12] and in contrary to three Brazilian studies [8, 13, 19]. We found palmar PH to be slightly more prevalent than plantar PH, in accordance to studies in Brazil [13, 19], whereas the studies in Germany and Sweden found plantar hyperhidrosis to be slightly more prevalent than palmar hyperhidrosis.…”
Section: Discussionsupporting
confidence: 87%
“…[12] Similarly, a Brazilian study also diagnosed 29.4% of patients reporting excessive sweating as SH. [19] This suggests that differences in diagnostic criteria for primary or secondary presentations may be responsible for variability of PH prevalence rather than epidemiological differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperhidrosis occurs as a result of increased sympathetic activity and may cause significant psychological problems and professional and social handicaps. [1] Hasimoto et al [2] stated that actual prevalence of primary hyperhidrosis was 0.93% and nearly 50% of the respondents with primary hyperhidrosis reported impaired quality of life. Although treatments such as botulinum toxin type A, oral medication, topical therapy with aluminium chloride, psychotherapy, and iontophoresis are available, surgical sympathectomy is being increasingly utilized.…”
mentioning
confidence: 99%
“…[1][2][3][4] İnsidansı tam olarak bilinmese de yapılan çalışmalarda genel olarak toplumun %0,6-4,8'inde görüldüğü rapor edilmiştir. [5][6][7] Terlemenin dağılımına göre sistemik veya lokalize olabilir ve terleme nedenine göre primer veya sekonder olarak sınıflandırılabilir. 8 Sistemik HH'de tüm vücutta terleme olur iken, lokalize terleme vücudun sadece belirli bölgelerini etkiler.…”
unclassified